Impact of personality traits on prosthodontic patients - Fernando Filipe dos Santos Dantas; Carlos Emanuel Natividade Ferreira de Almeida; André Ricardo Maia Correia; José Carlos Reis Campos (Universidade Estadual de Campinas, 2020)
Determining oral health-related quality of life in elderly patientswith removable prostheses who have increased difficulty inreporting oral issues is imperative for a successful rehabilitation.Aim: Our objective is to assess the extent to which a trace,or personality dimension, can influence oral health-relatedquality of life (OHRQoL) in rehabilitated patients. Methods:135 participants rehabilitated with removable prosthesis wereevaluated in the Clinical Unit of Removable Prosthodontics ofthe Faculty of Dental Medicine of Porto University, Portugal. TheOral Health Impact Profile (OHIP-14) questionnaire was appliedto evaluate oral health-related quality of life, along with theEysenck Personality Inventory (E.P.I.) to determine a personalitytrait. Statistical analysis was carried out using Mann-Whitney,Student's t-test, Spearman's rho and linear regression. Results:No statistical correlation was found concerning age, gender andoral health-related quality of life. Regarding the latter, the highestagreement was found on the question involving "pain in teeth".The prevalence of acrylic partial dentures, as opposed to partialdentures with metallic framework, was substantially higher. Nosigniﬁcant association between both extraversion/neuroticism(E.P.I.) and oral health-related quality of life (OHIP-14) uponrehabilitation with removable prostheses was found (p>0,05).In our study, personality traits neuroticism and extraversion didnot influence oral health-related quality of life with removableprostheses. However, we should not overlook the importance ofother psychological factors (such as motivation or perception)and their role in determining oral health-related quality of life.Conclusion: Personality traits "extraversion" and "neuroticism"did not influence oral health-related quality of life.